Pengintegrasian Teknologi Informasi dan Komunikasi dalam Pendidikan - Seipah Kardipah; Syarif Hidayatullah (Universitas Mathla'ul Anwar Banten, 2022)
ICT INTEGRATION IN EDUCATION. In the 21st century, teachers and students are required to have information and communication technology (ICT) capabilities. Teachers are required to integrate ICT in their daily teaching and learning activities. This study aims to (1) identify the level of computer skills and knowledge of junior high school teachers in learning, and (2) identify the level of integration of ICT in the teaching and learning process. A total of 25 teachers from a junior high school in Cirebon have been selected to complete this quantitative study’s survey questionnaire. The findings revealed that most of the teachers had basic computer skills and knowledge. Moreover, results show that some teachers have integrated ICT in their teaching and learning activities. However, more support is needed for teachers to be able to access training or seminars related to ICT for teaching and learning. Further research can be conducted to look at other aspects of integrating ICT in education, such as learning strategies and policies related to ICT for teaching and learning.